Service quality and customer satisfaction of low cost carried on pre-flight, in-flight, and post flight; a case of Malindo Air / Aini Nazirah Ahman, Muhammad Nabil Fikri Razman and Zainul Ariffin Abu Bakar - Ahman, Aini Nazirah; Razman, Muhammad Nabil Fikri; Abu Bakar, Zainul Ariffin (2015)
Low cost carrier or low-cost airline refer to the airline that provided the basic need with the no-frills, discounted or budgeted carrier in exchanges for eliminating the traditional passenger services. The Malaysia home-grown have several low-cost carriers such as Air Asia, Firefly, and Malindo Air. Therefore, this study focus on the customer satisfaction toward three stages; pre-flight, in-flight, and post-flight on the choose airline, Malindo Air. There were 210 questionnaires distributed during the duration of the survey. However, only 195 questionnaires were found to be valid and used for data analysis. Through the keyed data on SPSS version 23 shows that the most satisfied the passengers are during in-flight and post flight. The result revealed that “tangible”, “frequent flyer”, “timeliness”, “courtesy and language”, “responsiveness”, and “reliability”. However, only “tangible” and “frequent flyer” contributes significantly to the prediction of satisfaction on the services of low-cost carrier, Malindo Air.